Supramolecular metal complex with adjustable hydrogen bond strength and preparation method of supramolecular metal complex
By using PVP to adjust the hydrogen bond strength in the preparation process of supramolecular metal complexes, the problems of complex synthesis methods and poor product stability in the prior art are solved, and efficient and stable supramolecular metal complex preparation is achieved, and its application in the fields of catalysis and energy conversion is expanded.
Patent Information
- Application Number
- CN202411726022.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the method of synthesizing supramolecular metal complexes with hydrogen bond networks is complex, the product stability is poor, the yield is low, and it is difficult to effectively regulate the hydrogen bond strength, which limits its application in the fields of catalysis, energy conversion, etc.
Polyvinylpyrrolidone (PVP) is used as a regulator, and PVP is dissolved in water and reacted with Cu salt and strong alkali to form a surfactant micelle system, then ligand is added and heated to self-assemble, and hydrogen bond strength is regulated by controlling the amount of PVP.
The controllability of hydrogen bond strength in supramolecular metal complexes is achieved, and the obtained product has stability and high yield, which is suitable for catalysis and energy conversion fields.
Smart Images

Figure CN119570054A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of materials, and relates to functional supramolecular materials, and specifically to a supramolecular metal complex with adjustable hydrogen bond strength and a preparation method thereof. Background Art
[0002] Supramolecular metal complexes are molecular clusters with fixed composition formed by metal complex molecules through hydrogen bonding. Hydrogen bonds show rich variability in supramolecular metal complexes, which can provide precisely controllable structural and spatial environments for heterogeneous catalysis, molecular recognition, chemical sensing, electrochemical cells, etc. Therefore, supramolecular metal complexes have a wide range of application value and are currently a hot topic in the synthesis and preparation of supramolecular materials.
[0003] In addition, supramolecular metal complexes with hydrogen bond networks are widely used in catalysis, including photoelectrocatalytic synthesis, selective catalytic oxidation or reduction, lithium-ion battery electrode materials, sodium-ion battery electrode materials, etc. This is because hydrogen bonds can affect the state and reaction path of chemical reaction intermediates; supramolecular metal complexes can adjust the adsorption state and position of reaction intermediates by designing the strength of hydrogen bond networks, thereby improving the selectivity of reactions. The design and synthesis of catalysts with this structure have attracted many researchers in the field of catalysis.
[0004] At present, the methods for synthesizing supramolecular metal complexes with hydrogen bond networks mainly include two categories: (1) using external forces such as sound waves, vibration, grinding, shear mixing and freeze-thaw to break the weak interlayer interaction - hydrogen bonding; (2) destroying the hydrogen bond network through specific solvents or inserted molecules. However, these methods are not only too cumbersome in preparation, but also the resulting nanosheets are poorly uniform, low in yield, unstable, and easy to re-stacking, which seriously restricts the regulation of the hydrogen bond network in supramolecular metal complexes and limits the application of supramolecular metal complexes. Therefore, although supramolecular metal complexes with hydrogen bond networks have great application prospects in catalysis, energy conversion, coupling of different properties and steric effects, the currently reported supramolecular metal complexes of this type are very scarce and cannot meet actual needs.
[0005] Therefore, providing a method for preparing supramolecular metal complexes with simple steps, controllable hydrogen bond strength and stable products is a technical problem that needs to be solved urgently, which is of great significance for scientific research and industrial development. Summary of the invention
[0006] In view of the current status of the preparation method of supramolecular metal complexes with hydrogen bond networks in the prior art, the present invention provides a new preparation method of supramolecular metal complexes with hydrogen bond networks. The preparation method is not only simple to operate and has stable products, but also can achieve the regulation of hydrogen bond strength in supramolecular metal complexes by regulating the preparation conditions, thus achieving unexpected technical effects.
[0007] The technical solution of the present invention:
[0008] A method for preparing a supramolecular metal complex having a hydrogen bond network comprises the following steps:
[0009] (1) First, an appropriate amount of polyvinyl pyrrolidone (PVP) is dissolved in water at 40-50°C to obtain a PVP solution. Then, an appropriate amount of a strong base and a Cu salt are placed in the aforementioned PVP solution, and ultrasonicated or stirred at 5-10°C until the two are completely dissolved to obtain a surfactant micelle system in which Cu ions are uniformly dispersed, i.e., system I.
[0010] The molar ratio of PVP, strong base and Cu salt is (1-4): 1:1; the amount of water is 15 to 30 times the total mass of the solid reactants. The average molecular weight of the PVP is 24000-50000; the strong base is sodium hydroxide, potassium hydroxide or lithium hydroxide, and the Cu salt is copper acetate monohydrate or copper nitrate trihydrate.
[0011] (2) Add an appropriate amount of ligand to system I and stir at room temperature for 20-60 min to dissolve and evenly disperse the ligand, which then coordinates with Cu to form dispersed metal complex molecules, thereby obtaining a metastable system before self-assembly, namely system II.
[0012] Wherein, the ligand is 2,2'-bipyridine, 1,10-phenanthroline, 2-(3H-pyrrol-2-yl)pyridine or 5H-cyclopentadiene-[2,1-b:3,4-b']bipyridine; and the molar ratio of the ligand to the Cu salt is 1:1.
[0013] (3) Transferring system II to a sealed container, heating at 160°C for 90-120 hours, and cooling to room temperature at a cooling rate of 5-25°C / h; filtering, washing, and drying to obtain a supramolecular metal complex with a hydrogen bond network. The washing solvents are water and ethanol; the drying is specifically: drying at 40-80°C overnight.
[0014] The inventor unexpectedly discovered that the supramolecular metal complex prepared by adding PVP to the system achieved isotropic growth in one dimension. Not only was the preparation method simple and the yield high, but the prepared nanosheets were also stable. This solved the technical problems of the prior art, which had complicated preparation methods, poor stability of the prepared nanosheets, and low yield, and achieved unexpected technical effects.
[0015] The present application also provides a supramolecular metal complex with a hydrogen bond network prepared by the aforementioned method; the supramolecular metal complex is a one-dimensional isotropically grown supramolecular metal complex. In the supramolecular metal complex, the OO of C=O of the PVP molecule is attached to the Cu···Cu surface of the metal complex to prevent the formation of hydrogen bonds. Therefore, by changing the amount of PVP, macro-control of the number of hydrogen bonds in the supramolecular metal complex can be achieved, that is, the strength of hydrogen bonds can be controlled. The inventor speculates through research that this is because the theoretical distance between the functional groups (C=O) with adhesion ability in the PVP molecule is A pair of Cu ions in the Cuobpy molecule exhibits short intramolecular Cu···Cu contacts The PVP molecules perfectly combined with the Cu center, and there was an adsorption interaction between the C=O and Cu sites, which made the bottom-up assembly of the supramolecular possible.
[0016] The application of the supramolecular metal complex with a hydrogen bond network as described above. Preferably, the application is used as a catalyst for electrocatalytic reduction reaction. The supramolecular metal complex with a hydrogen bond network prepared in the present application not only has controllable hydrogen bond strength, but also has good crystallinity, and has good application prospects in catalytic organic synthesis, drug sustained release, electrochemical energy storage, etc.
[0017] Preparation principle (explained with 2,2'-bipyridine as ligand):
[0018] [HCuobpy] is a cluster of Cuobpy molecules connected by a hydrogen bond network; each copper ion in the HCuobpy unit is coordinated to two N atoms on one Cuobpy ligand and one O atom on the other ligand. In the HCuobpy supramolecule, the Cu-coordinated O atoms form hydrogen bonds (O···HC) with the CH on the benzene ring of the adjacent Cuobpy molecule.
[0019] After the introduction of PVP, due to the OO spacing of C=O in the PVP molecule The Cu…Cu distance within the molecule in the metal complex Very close (see attached Figure 1), so that there is an adsorption interaction between C=O and Cu sites. Moreover, the hydrogen bond formation rate between O and CH shows slower kinetics compared with the adsorption rate between C=O and Cu sites in PVP. Therefore, PVP has a significant inhibitory effect on the formation of hydrogen bonds between metal complexes during the assembly of supramolecular metal complexes, thereby achieving controllable and stable regulation of hydrogen bonds.
[0020] Furthermore, after the introduction of PVP, it not only inhibits the formation of hydrogen bonds, but also adjusts the distribution of associated atoms in the original hydrogen bond network, changes the stacking mode of the metal complex, and extends the product morphology from nanostrips to nanosheets, thereby realizing the bottom-up synthesis of supramolecular metal complexes with hydrogen bond networks. In summary, compared with conventional hydrogen bond regulation methods, the preparation method described in this application can achieve the regulation of hydrogen bond strength and surface chemical properties, and is easy to achieve large-scale production.
[0021] Beneficial effects of the present invention:
[0022] (1) The present invention proposes a new method for preparing supramolecular metal complexes with hydrogen bond networks. The preparation method is not only simple to operate and produces stable products, but also can achieve regulation of hydrogen bond strength in supramolecular metal complexes by regulating the preparation conditions, thus achieving unexpected technical effects.
[0023] (2) The preparation method described in the present invention innovatively introduces PVP, which is attached to the supramolecular metal complex through the adsorption effect between the C=O and Cu sites in PVP. This not only inhibits the formation of hydrogen bonds between the metal complexes during the assembly process of the supramolecular metal complex, but also limits the longitudinal stacking of the metal complex layers, thereby obtaining a supramolecular metal complex that grows isotropically in one dimension, filling the gap in the prior art.
[0024] (3) The supramolecular metal complex with a hydrogen bond network prepared in the present application can adjust the dispersion degree of the associated atomic distribution in the hydrogen bond network by changing the dosage of PVP, thereby achieving precise regulation of the hydrogen bond network; thereby effectively regulating the spatial environment of the supramolecular metal complex, further expanding its scope of application. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Attached Figure 1 For PVP fragment model and OO spacing Model and Cu…Cu distance of Cuobpy molecule Model.
[0026] Attached Figure 2 P prepared in Examples 1-3 of the present application x XRD spectra of Cuobpy crystal and HCuobpy crystal prepared in comparative example.
[0027] Attached Figure 3 P prepared in Examples 1-3 of the present application x Thermogravimetric analysis spectra of Cuobpy crystals and HCuobpy crystals prepared in comparative example under air conditions.
[0028] Attached Figure 4 P prepared in Examples 1-3 of the present application x Fourier transform infrared spectra of Cuobpy crystal and HCuobpy crystal prepared in comparative example.
[0029] Attached Figure 5 P prepared in Examples 1-3 of the present application x 2D Raman spectra of Cuobpy crystal and HCuobpy crystal prepared in comparative example.
[0030] Attached Figure 6 Electron microscopy is the P prepared in Examples 1-3 of this application x TEM images of Cuobpy crystals and HCuobpy crystals prepared in comparative example at the same scale.
[0031] Attached Figure 7 In 0.1M KHCO3 electrolyte, HCuobpy and P at different potentials 2 Faradaic efficiency of Cuobpy electrolysis for 20 min. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the examples. Other purposes and advantages of the present invention will become clear by explaining the following preferred embodiments of the present application.
[0033] The raw materials used in this application were purchased through commercial channels, and all reagents were not further purified before use. Among them, copper acetate monohydrate (Cu(CH3COO)2·H2O, 99%), copper nitrate trihydrate (Cu(NO3)2·3H2O), 2,2'-bipyridine (bpy, 99%), 1,10-phenanthroline (phen, 99%), 2-(1H-pyrrol-2-yl)pyridine (ppy, 99%), 5H-cyclopentadiene-[2,1-b:3,4-b']bipyridine (cdpy, 99%), sodium hydroxide (NaOH, 99%), potassium hydroxide (KOH, 99%), and lithium hydroxide (LiOH, 99%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; polyvinylpyrrolidone (PVP, K30) was purchased from Sinopharm Chemical Co., Ltd. Weighing balance: Shimadzu AUX220 (accurate to 0.1 mg)
[0034] The above reagents are only used to further illustrate the raw materials and reagents used in the examples, and are not intended to further limit the scope of protection.
[0035] Example 1: Preparation of supramolecular metal complexes with hydrogen bond networks
[0036] (1) 0.11 g of polyvinyl pyrrolidone (PVP, average molecular weight 40,000) was dissolved in 6 g of water at 45°C to obtain a PVP solution. Then, 0.04 g of sodium hydroxide and 0.20 g of copper acetate monohydrate were placed in the aforementioned PVP solution, and ultrasonicated at 5°C until the two were completely dissolved to obtain a surfactant micelle system in which Cu ions were uniformly dispersed, i.e., system I. The molar ratio of the aforementioned PVP, strong base and Cu salt was 1:1:1; the amount of water used was 17 times the total mass of the solid reactants.
[0037] (2) Add 0.156 g of 2,2'-bipyridine (structure shown below) to system I and stir at room temperature for 30 min to dissolve and evenly disperse the ligand, which then coordinates with Cu to form dispersed metal complex molecules, thereby obtaining a metastable system before self-assembly, namely system II. The molar ratio of the above ligand to the Cu salt is 1:1.
[0038]
[0039] (3) System II was transferred to a sealed container, heated at 160°C for 90 hours, and then cooled to room temperature at a cooling rate of 5°C / h; after filtering, washing, and drying, a supramolecular metal complex with a hydrogen bond network, namely, P 1 Cuobpy crystals. The washing solvents are water and ethanol; the drying is specifically: drying at 60°C overnight.
[0040] Example 2: Preparation of supramolecular metal complexes with hydrogen bond networks
[0041] Different from Example 1,
[0042] (1) The amount of PVP used is 0.22 g. The molar ratio of the PVP, strong base and Cu salt is 2:1:1; the amount of water used is 13 times the total mass of the solid reactants.
[0043] (2) Same as Example 1.
[0044] (3) As in Example 1, the obtained supramolecular metal complex P 2 Cuobpy crystals.
[0045] Example 3: Preparation of supramolecular metal complexes with hydrogen bond networks
[0046] Different from Example 1,
[0047] (1) The amount of PVP used is 0.44 g. The molar ratio of the above-mentioned PVP, strong base and Cu salt is 4:1:1; the amount of water used is 8.8 times the total mass of the solid reactants.
[0048] (2) Same as Example 1.
[0049] (3) As in Example 1, the obtained supramolecular metal complex P 3 Cuobpy crystals.
[0050] Example 4: Preparation of supramolecular metal complexes with hydrogen bond networks
[0051] Different from Example 1,
[0052] (1) 0.22 g of PVP (average molecular weight of 20,000) was dissolved in 15.51 g of water at 40°C to obtain a PVP solution. Then, 0.056 g of potassium hydroxide and 0.241 g of copper nitrate trihydrate were placed in the aforementioned PVP solution, and ultrasonicated at 8°C until the two were completely dissolved to obtain a surfactant micelle system in which Cu ions were uniformly dispersed, i.e., system I. The molar ratio of the aforementioned PVP, strong base, and Cu salt was 2:1:1; the amount of water used was 30 times the total mass of the solid reactants.
[0053] (2) Add 0.180 g of ligand 1,10-phenanthroline (structure shown in the following formula) to system I, and stir at room temperature for 20 min to dissolve and evenly disperse the ligand, and then coordinate with Cu to form dispersed metal complex molecules, thereby obtaining a metastable system before self-assembly, namely system II. The molar ratio of the above ligand to the Cu salt is 1:1.
[0054]
[0055] (3) Transferring system II to a sealed container, heating at 160°C for 100 hours, and cooling to room temperature at a cooling rate of 20°C / h; filtering, washing, and drying to obtain a supramolecular metal complex with a hydrogen bond network, namely, PCuophen crystals. The washing solvents used are water and ethanol; and the drying is specifically: drying at 60°C overnight.
[0056] Example 5: Preparation of supramolecular metal complexes with hydrogen bond networks
[0057] Different from Example 1,
[0058] (1) 0.33 g of polyvinyl pyrrolidone (PVP, average molecular weight 58000) was dissolved in 8.79 g of water at 45°C to obtain a PVP solution. Then 0.056 g of potassium hydroxide and 0.20 g of copper acetate monohydrate were placed in the aforementioned PVP solution, and ultrasonicated at 10°C until the two were completely dissolved to obtain a surfactant micelle system in which Cu ions were uniformly dispersed, i.e., system I. The molar ratio of the aforementioned PVP, strong base and Cu salt was 3:1:1; the amount of water used was 15 times the total mass of the solid reactants.
[0059] (2) Add 0.168 g of ligand 5H-cyclopentadiene-[2,1-b:3,4-b']bipyridine (structure shown in the following formula) to system I, and stir at room temperature for 30 min to dissolve and evenly disperse the ligand, and then coordinate with Cu to form dispersed metal complex molecules, thereby obtaining a metastable system before self-assembly, namely system II. The molar ratio of the above ligand to the Cu salt is 1:1.
[0060]
[0061] (3) Transferring system II to a sealed container, heating at 160°C for 110 hours, and cooling to room temperature at a cooling rate of 25°C / h; filtering, washing, and drying to obtain a supramolecular metal complex with a hydrogen bond network, namely, PCuocdpy crystals. The washing solvents used are water and ethanol; and the drying is specifically: drying at 80°C overnight.
[0062] Example 6: Preparation of supramolecular metal complexes with hydrogen bond networks
[0063] Different from Example 1,
[0064] (1) 0.44 g of polyvinyl pyrrolidone (PVP, average molecular weight 40000) was dissolved in 13.92 g of water at 50°C to obtain a PVP solution. Then 0.056 g of potassium hydroxide and 0.20 g of copper acetate monohydrate were placed in the aforementioned PVP solution, and ultrasonicated at 5°C until the two were completely dissolved to obtain a surfactant micelle system in which Cu ions were uniformly dispersed, i.e., system I. The molar ratio of the aforementioned PVP, strong base and Cu salt was 4:1:1; the amount of water used was 20 times the total mass of the solid reactants.
[0065] (2) 0.144 g of ligand 2-(3H-pyrrol-2-yl)pyridine (structure shown below) was added to system I and stirred at room temperature for 40 min to dissolve and evenly disperse the ligand, and then coordinate with Cu to form dispersed metal complex molecules to obtain a metastable system before self-assembly, i.e., system II. The molar ratio of the above ligand to the Cu salt was 1:1.
[0066]
[0067] (3) Transfer system II to a sealed container, heat at 160°C for 120 hours, and then cool to room temperature at a cooling rate of 10°C / h; filter, wash, and dry to obtain a supramolecular metal complex with a hydrogen bond network, namely PCuoppy crystals. The washing solvents are water and ethanol; the drying is specifically: drying at 40°C overnight.
[0068] Example 7: Preparation of supramolecular metal complexes with hydrogen bond networks
[0069] The difference from Example 1 is that PVP is dissolved in 10.5 g of water.
[0070] (1) 0.11 g of polyvinyl pyrrolidone (PVP, average molecular weight 58000) was dissolved in 9.38 g of water at 50°C to obtain a PVP solution. Then 0.024 g of lithium hydroxide and 0.241 g of copper nitrate trihydrate were placed in the aforementioned PVP solution, and ultrasonicated at 10°C until the two were completely dissolved to obtain a surfactant micelle system in which Cu ions were uniformly dispersed, i.e., system I. The molar ratio of the aforementioned PVP, strong base and Cu salt was 1:1:1; the amount of water used was 25 times the total mass of the solid reactants.
[0071] (2) Add 0.180 g of ligand 1,10-phenanthroline (structure shown below) to system I and stir at room temperature for 50 min to dissolve and evenly disperse the ligand, and then coordinate with Cu to form dispersed metal complex molecules to obtain a metastable system before self-assembly, i.e., system II. The molar ratio of the above ligand to the Cu salt is 1:1.
[0072]
[0073] (3) Transferring system II to a sealed container, heating at 160°C for 90 hours, and cooling to room temperature at a cooling rate of 20°C / h; filtering, washing, and drying to obtain a supramolecular metal complex with a hydrogen bond network, namely, PCuophen crystals. The washing solvents used are water and ethanol; and the drying is specifically: drying at 50°C overnight.
[0074] Example 8: Preparation of supramolecular metal complexes with hydrogen bond networks
[0075] Different from Example 1,
[0076] (1) 0.44 g of polyvinyl pyrrolidone (PVP, average molecular weight 20000) was dissolved in 19.92 g of water at 40°C to obtain a PVP solution. Then 0.024 g of lithium hydroxide and 0.20 g of copper acetate monohydrate were placed in the aforementioned PVP solution, and ultrasonicated at 8°C until the two were completely dissolved to obtain a surfactant micelle system in which Cu ions were uniformly dispersed, i.e., system I. The molar ratio of the aforementioned PVP, strong base and Cu salt was 4:1:1; the amount of water used was 30 times the total mass of the solid reactants.
[0077] (2) 0.144 g of ligand 2-(3H-pyrrol-2-yl)pyridine (structure shown below) was added to system I and stirred at room temperature for 60 min to dissolve and evenly disperse the ligand, and then coordinate with Cu to form dispersed metal complex molecules to obtain a metastable system before self-assembly, i.e., system II. The molar ratio of the above ligand to the Cu salt was 1:1.
[0078]
[0079] (3) Transfer system II to a sealed container, heat at 160°C for 100 hours, and then cool to room temperature at a cooling rate of 15°C / h; filter, wash, and dry to obtain a supramolecular metal complex with a hydrogen bond network, namely PCuoppy crystals. The washing solvents used are water and ethanol; the drying is specifically: drying at 70°C overnight.
[0080] Comparative Example 1: Preparation of HCuobpy Crystals
[0081] A mixture of Cu(CH3COO)2·H2O (0.200 g, 1.0 mmol), bpy (0.156 g, 1.0 mmol), NaOH (0.040 g, 1124 mmol), and H2O (6 mL) was added to a 15 mL stainless steel container, heated at 160°C for 96 h, and then cooled to room temperature. The mixture was filtered, and the black crystals (HCuobpy) were washed several times with deionized water and dried in a vacuum oven at 60°C to obtain HCuobpy crystals.
[0082] Example 9: Structural Characterization of Products
[0083] The crystals prepared in Examples 1-8 of the present application and the HCuobpy crystals prepared in Comparative Example 1 were characterized by X-ray powder diffractometer, Fourier transform infrared spectrometer and Raman spectroscopy. The characterization results of the crystals prepared in Examples 1-8 are similar, and are now described below using Example 1-3 as an example.
[0084] Attached Figure 2 P prepared in Examples 1-3 of the present application xXRD spectra of Cuobpy crystals and HCuobpy crystals prepared in Comparative Example 1. The product prepared in Comparative Example 1 is composed of Cuobpy molecules and has good crystallinity. Figure 2 It can be seen that the product prepared in this application is also composed of Cuobpy molecules and has good crystallinity. Moreover, with the increase in the amount of PVP, the diffraction peak of the Cu-O crystal plane becomes sharper and stronger; this indicates that the physical crosslinking density and crystallinity of the Cuobpy molecules in the product prepared in this application have changed. This can be attributed to the spatial interaction of the surfactant, which hinders the interaction (hydrogen bond interaction) inside the Cuobpy crystal.
[0085] Attached Figure 3 P prepared in Examples 1-3 of the present application x Thermogravimetric analysis spectra of Cuobpy crystals and HCuobpy crystals prepared in Comparative Example 1 under air conditions. Figure 3 It can be seen that the weight of HCuobpy decreases significantly at 286℃, while P 1 Cuobpy, P 2 Cuobpy and P 3 The weight of Cuobpy decreased significantly at 274°C, 260°C and 253°C. x The decomposition temperature of Cuobpy crystals gradually decreased slightly. This preliminarily indicates that PVP hinders the formation of hydrogen bonds O···HC. At the same time, the decomposition temperature of HCuobpy prepared in Comparative Example 1 is slightly higher, indicating the existence of hydrogen bonds O···HC.
[0086] Attached Figure 4 P prepared in Examples 1-3 of the present application x Fourier transform infrared spectra of Cuobpy crystal and HCuobpy crystal prepared in comparative example. Figure 4 a It can be seen that the stretching vibration of C=O in PVP appears at 1667cm -1 With the introduction of PVP, x 1667cm appeared in Cuobpy -1 This indicates that the C=O group in PVP is successfully attached to the Cu center. In addition, the C=O peak at 2958 cm -1 The peak at about 3060 cm corresponds to the CH vibration in PVP. -1 The peaks at correspond to HCuobpy and P x CH vibration in Cuobpy. Figure 4 b It can be seen that compared with HCuobpy, P xThe CH contraction vibration position of Cuobpy shifts slightly to a higher wave number, indicating that the breakage of O···HC is weakened and the stretching effect of O on H is weakened. -1 There are significant negative peaks around the CH vibration peak, showing a trend of gradual decrease, indicating that the breakage of O···HC is weakened. Figure 3 The results are consistent. However, the CH contraction vibration position wave number of HCuobpy prepared in Comparative Example 1 is the lowest, and the CH peak is the strongest, which is due to the CH stretching vibration caused by hydrogen bonding.
[0087] Attached Figure 5 P prepared in Examples 1-3 of the present application x 2D Raman spectra of Cuobpy crystals and HCuobpy crystals prepared in comparative examples. Figure 5 The 2D Raman spectrum of the P prepared in this application can also be seen. x Cuobpy crystals at 3058-3060cm -1 The Raman spectrum further proves that PVP hinders the formation of hydrogen bonds O···HC, which is related to the Figure 3 The results are consistent.
[0088] Attached Figure 6 Electron microscopy is the P prepared in Examples 1-3 of this application x TEM images of Cuobpy crystals and HCuobpy crystals prepared in the comparative example at the same scale. Figure 6 It can be seen that HCuobpy presents a linear structure. 2 Cuobpy shows a nanosheet structure with a smooth surface. These results indicate that the addition of PVP changes the crystal morphology, leading to a change in the self-assembly mode of Cuobpy molecules and achieving the regulation of hydrogen bonds O···HC.
[0089] Example 10: Electrocatalytic reduction of CO2 experiment
[0090] Take P prepared in Examples 1-3 of this application X Cuobpy crystals and HCuobpy crystals prepared in Comparative Example 1 were subjected to electrocatalytic reduction of CO2 experiments respectively.
[0091] Experimental steps: Glassy carbon or carbon paper (GDL) containing catalyst was used as the working electrode. Electrochemical measurements were performed in an H-type cell with a three-electrode system and Nafion 117 membrane as the separation membrane using an electrochemical workstation (Gamery Interface 1010E). Ag / AgCl electrode and platinum electrode were used as the reference electrode and counter electrode, respectively. 0.1M KHCO3 aqueous solution was used as the electrolyte. After carbon dioxide (99.99%) was continuously bubbling for more than 30 min, constant voltage electrolysis was performed. During the entire electrolysis process, the average rate of CO2 entering the cathode electrolyte was 30 mL min -1 .
[0092] (1) P prepared in Examples 1-3 of the present application X The results of the Cuobpy crystal electrocatalytic reduction of CO2 are as follows: In 0.1M KHCO3 aqueous solution, H2, CO, CH4 and C2H4 are the main gaseous products, and no liquid products are detected. The three catalysts have significant differences in product selectivity, showing different Faraday efficiencies for CH4 and C2H4, respectively. Figure 7 ). Among them, P 2 Cuobpy has the highest selectivity for C2H4 (60.1%), exceeding P 1 Cuobpy and P 3 With the over-adhesion of PVP, the exposure of the dual Cu sites was significantly reduced, and P 3 The generation of C2H4 on Cuobpy is no longer prominent.
[0093] (2) The results of the electrocatalytic reduction of CO2 by HCuobpy crystals prepared in Comparative Example 1 are as follows: In 0.1M KHCO3 aqueous solution, H2, CO, CH4 and C2H4 are the main gaseous products, and no liquid products are detected. The main product of HCuobpy is CH4, and the highest FE of CH4 reaches 59.4%.
[0094] This shows that the P prepared in Examples 1-3 of the present application X Cuobpy crystals and HCuobpy crystals prepared in Comparative Example 1 can both be used as catalysts for electrocatalytic reduction of CO2, but the products are quite different. X Cuobpy crystals, the products are not exactly the same. This just shows that the P prepared in Examples 1-3 of this application X Cuobpy crystals achieve control over the strength of hydrogen bonds, thereby regulating the spatial environment of supramolecular metal complexes and affecting the catalytic products.
[0095] In summary, the present invention provides a new method for preparing supramolecular metal complexes with hydrogen bond networks. The preparation method innovatively introduces PVP, which inhibits the formation of hydrogen bonds between metal complexes during the assembly process of supramolecular metal complexes, and limits the longitudinal stacking of metal complex layers, thereby obtaining supramolecular metal complexes that grow isotropically in one dimension, filling the gap in the prior art, with simple operation and stable products. Not only that, the preparation method described in the present application can adjust the degree of dispersion of the distribution of associated atoms in the hydrogen bond network by changing the amount of PVP, thereby regulating the hydrogen bond strength in the product, and achieving unpredictable technical effects.
Claims
1. A method for preparing a supramolecular metal complex having a hydrogen bond network, characterized in that: The following steps are involved: (1) First, a proper amount of polyvinyl pyrrolidone (PVP) is dissolved in water at 40-50° C. to obtain a PVP solution; then, a proper amount of a strong base and a Cu salt are placed in the aforementioned PVP solution, and ultrasonically or stirred at 5-10° C. until the two are completely dissolved, to obtain system I; (2) adding an appropriate amount of ligand to system I and stirring at room temperature for 20-60 min to uniformly disperse the ligand and coordinate with Cu to obtain a metastable system before self-assembly, i.e., system II; (3) Transferring system II to a sealed container, heating at 160° C. for 90-120 hours, and cooling to room temperature; filtering, washing, and drying to obtain a supramolecular metal complex with a hydrogen bond network.
2. The method for preparing a supramolecular metal complex according to claim 1, characterized in that: In step (1), the molar ratio of PVP, strong base and Cu salt is (1-4): 1:1; the amount of water used is 15 to 30 times the total mass of the solid reactants.
3. The method for preparing a supramolecular metal complex according to claim 2, characterized in that: In step (1), the average molecular weight of PVP is 24000-50000; the strong base is sodium hydroxide, potassium hydroxide or lithium hydroxide, and the Cu salt is copper acetate monohydrate or copper nitrate trihydrate.
4. The method for preparing a supramolecular metal complex according to claim 3, characterized in that: The ligand in step (2) is 2,2'-bipyridine, 1,10-phenanthroline, 5H-cyclopentanone-[2,1-b:3,4-b']bipyridine or 2-(3H-pyrrol-2-yl)pyridine; the molar ratio of the ligand to the Cu salt is 1:
1.
5. The method for preparing a supramolecular metal complex according to any one of claims 1 to 4, characterized in that: The cooling rate of the cooling step in step (3) is 5-25°C / h.
6. The method for preparing a supramolecular metal complex according to claim 5, characterized in that: The solvents used for washing in step (3) are water and ethanol; the drying is specifically: drying at 40-80°C overnight.
7. A supramolecular metal complex having a hydrogen bond network prepared by any one of claims 1 to 6.
8. The supramolecular metal complex having a hydrogen bond network according to claim 7, characterized in that: The supramolecular metal complex is a one-dimensional isotropically grown supramolecular metal complex.
9. The supramolecular metal complex having a hydrogen bond network according to claim 7, characterized in that: In the supramolecular metal complex, the OO of C═O of the PVP molecule is attached to the Cu···Cu surface of the metal complex, thereby preventing the formation of hydrogen bonds.
10. Use of the supramolecular metal complex according to any one of claims 7 to 9, characterized in that: The application is for electrocatalytic reduction reaction.